Nanoseparation Using Density Gradient Ultracentrifugation Mechanism, Methods and Applications - Sun, Xiaoming; Luo, Liang; Kuang, Yun; Li, Pengsong (SpringerBriefs in Molecular Science, 2018)
This book introduces the classification and mechanism of density gradient ultracentrifugation (DGUC) method with rich examples showing the versatility of such an efficient separation technique. It also gives a strict mathematical description and a computational optimization model to predict the best separation parameters for a given colloidal system. The concept of "Lab in a tube" is proposed in the last chapter, which allows the size-property relationship investigation, synthetic optimization and reaction/assembly mechanism exploration etc. .